Selection of the Recommended Phase 2 Dose for Bintrafusp Alfa, a Bifunctional Fusion Protein Targeting TGF‐β and PD‐L1. Issue 3 (3rd March 2020) - Vugmeyster, Yulia; Wilkins, Justin; Koenig, Andre; El Bawab, Samer; Dussault, Isabelle; Ojalvo, Laureen S.; De Banerjee, Samrita; Klopp‐Schulze, Lena; Khandelwal, Akash
Abstract : Bintrafusp alfa, a first‐in‐class bifunctional fusion protein composed of the extracellular domain of the TGF‐βRII receptor (TGF‐β "trap") fused to a human IgG1‐blocking PD‐L1, showed a manageable safety profile and clinical activity in phase I studies in patients with heavily pretreated advanced solid tumors. The recommended phase 2 dose (RP2D) was selected based on integration of modeling, simulations, and all available data. A 1, 200‐mg every 2 weeks (q2w) dose was predicted to maintain serum trough concentration (Ctrough ) that inhibits all targets of bintrafusp alfa in circulation in > 95% of patients, and a 2, 400‐mg every 3 weeks (q3w) dose was predicted to have similar Ctrough . A trend toward an association between exposure and efficacy variables and a relatively stronger inverse association between clearance and efficacy variables were observed. Exposure was either weakly or not correlated with probability of adverse events. The selected intravenous RP2D of bintrafusp alfa is 1, 200 mg q2w or 2, 400 mg q3w.